Functional roles of circular RNAs in lung injury - Gao, Fei-Fei; Chen, Dian-Qing; Jiang, Yue-Tong; Han, Cui-Fei; Lin, Bi-Yun; Yang, Zhan; Quan, Juan-Hua; Xiong, Ying-Huan; Chen, Xin-Tian (Frontiers in Pharmacology, 2024)
Lung injury leads to respiratory dysfunction, low quality of life, and even life-threatening conditions. Circular RNAs (circRNAs) are endogenous RNAs produced by selective RNA splicing. Studies have reported their involvement in the progression of lung injury. Understanding the roles of circRNAs in lung injury may aid in elucidating the underlying mechanisms and provide new therapeutic targets. Thus, in this review, we aimed to summarize and discuss the characteristics and biological functions of circRNAs, and their roles in lung injury from existing research, to provide a theoretical basis for the use of circRNAs as a diagnostic and therapeutic target for lung injury.